Multi-stimuli-responsive magnetic assemblies as tunable releasing carriers1. Issue 29 (7th August 2015) - Zhang, Xiao-Mei; Guo, Kun; Li, Luo-Hao; Zhang, Sheng; Li, Bang-Jing
<x xml:space="preserve">Abstract</x> Construction of amphiphilic magnetic nanoparticles (MNPs) by cyclodextrin-based inclusion complexation and the reversible assembly of these MNPs triggered by temperature or redox reagent.